STUDI KOMPARATIF HIPERTENSI DI WILAYAH KERJA PUSKESMAS BONE ROMBO KABUPATEN BUTON UTARA TAHUN 2021 - Ayu Oktavia; La Ode Muhamad Sety; Ruwiah Ruwiah (Endemis Journal, 2022)
Hypertension is classified as one of the ten main causes of death for people around the world, especially those living in coastal and estuary areas. WHO data, shows that in 2019 around 1.13 billion people in the world suffer from hypertension, meaning that the data illustrates that 1 in 3 people in the world is diagnosed with hypertension. The increase in the incidence of hypertension is influenced by an unhealthy lifestyle. This study aims to determine the difference in lifestyle with the incidence of hypertension in coastal and non-coastal communities in the working area of Bone Rombo Health Center, North Buton Regency in 2021. This study is a quantitative study with a cross sectional study approach. The population in this study were all coastal communities in Lemo Village and non-coastal areas in Rombo Village with a total of 560 families who were within the working area of Bone Rombo Health Center. The sample in this study amounted to 85 respondents consisting of 40 respondents from coastal areas and 45 respondents from non-coastal areas, sampling using simple random sampling technique. The results showed that there was a significant difference in diet (fat intake p = 0.011 and sodium p = 0.000) and there was no significant difference in stress (p = 0.126) with the incidence of hypertension in coastal and non-coastal communities in the working area of Bone Rombo Health Center, North Buton Regency. 2021. The conclusion in this study is that the incidence of hypertension in coastal and non-coastal areas is relatively different, this is indicated by a significant difference in diet (fat and sodium intake).